PERAN KEPALA SEKOLAH DALAM PENYELENGGARAAN PENDIDIKAN INKLUSIF DI SMP NEGERI 4 JELAI HULU - Pasaribu, Rhendivan; Radiana, Usman; Wicaksana, Luhur; Dominico Panggoning Salarasati, Claudi (Universitas Muhammadiyah Surakarta, 2023)
This research illustrates the important role of the head of school in providing inclusive education in remote areas. School leaders have a central role to play in leading schools towards a vision of inclusive mission, influencing teacher performance, and creating an inclusive educational environment. Effective school leaders are able to analyze situations, make strategic decisions, and design inclusive educational programs that are tailored to the needs of students with special needs. School leaders also play a role in motivating and empowering teachers to support inclusive education. However, challenges such as limited resources and infrastructure in remote areas can affect the implementation of inclusion. Through a qualitative approach with interviews, observations, and documentation, the study obtained data on the role of the head of school in the development of inclusive education programs. The data shows that the head of the school has good managerial skills in managing teachers, designing inclusive programs, and regulating the distribution of teachers' duties. This inclusive education program includes the strengthening of the role of a special accompanying teacher, structured learning for students with special needs, fundraising and facilities, and improved teacher well-being. The leadership of the head of school in this inclusive education also requires close cooperation between all stakeholders, including teachers, parents, and other relevant parties. Despite the challenges, this study demonstrates the importance of the role of the head of school in achieving equal and inclusive education in remote areas